"The problem is people don't know how to talk to you:" How Medicaid recipients understand and use health plan report cards and instruction sheets. Issue 3 (3rd July 2018) - Goodman, J. Robyn; Duke, Lisa L.; Theis, Ryan P.; Shenkman, Elizabeth A.
Abstract: This study sought to understand low income, ethnically diverse individuals' needs, comprehension, and opinions of comparative quality information as presented in state Medicaid health plan report cards (HPRCs). Twenty-two focus groups were conducted with urban and rural Medicaid recipients in three ethnic groups. Results showed the wording of some domains was misunderstood and an overabundance of domains that are irrelevant to the individual attenuated attention. Combinations of visual and verbal information and well-organized designs aided attention and comprehension. Stating where the data came from was important. Some key differences between ethnicity and geographic areas were noted.